Cryptocurrency as A Main Currency: A Maqasidic Approach - Mohd Shahid Mohd Noh; Mohamed Syakir Abu Bakar (Universitas Negeri Surabaya, 2020)
Cryptocurrency is a new phenomenon in investment industry in particular and financial world in large. The opportunities and threats come one over another in cryptocurrency debate that left people in perplex state whether to accept or reject the currency. In other view, it also brings advantages and inevitable disadvantages since it is operated online that vulnerable to number of threats and danger. This paper tries to examine maqasid views on this currency relying on SWOT analysis then will be viewed on the mirror of maslahah dan mafsadah as main pillars in maqasid al-syariah. As a result, this issue needs to be studied further since the maslahah and mafsadah sometime interchange the roles as particular, general maslahah and its counterparty since the system is always been designed for the benefits, that yet created the negative implication simultaneously. Furthermore, this innovation could be designed followed the desire of designers with dynamics structure in fulfilling the markets needs.